2022
DOI: 10.3847/1538-4357/ac7964
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Hydrodynamical Shocks as the Smoking-gun Evidence for a Bar in M31

Abstract: The formation and evolutionary history of M31 are closely related to its dynamical structures, which remain unclear due to its high inclination. Gas kinematics could provide crucial evidence for the existence of a rotating bar in M31. Using the position–velocity diagram of [O III] and H i, we are able to identify clear sharp velocity jump (shock) features with a typical amplitude over 100 km s−1 in the central region of M31 (4.6 kpc × 2.3 kpc, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…A delay of 0.1-1 Gyr between quenching and a detectable change in the CGM is reasonable. M31 is also known to have a bar, and so could be passive due to internal dynamical effects that are irrelevant for its CGM (Athanassoula & Beaton 2006;Dorman et al 2015;Feng et al 2022).…”
Section: The Case Of M31mentioning
confidence: 99%
“…A delay of 0.1-1 Gyr between quenching and a detectable change in the CGM is reasonable. M31 is also known to have a bar, and so could be passive due to internal dynamical effects that are irrelevant for its CGM (Athanassoula & Beaton 2006;Dorman et al 2015;Feng et al 2022).…”
Section: The Case Of M31mentioning
confidence: 99%
“…Opitsch et al (2018) show that kinematics data support a bar in M31, with nontriaxial streaming motions. The presence of a bar is confirmed by Feng et al (2022) in the central 4.6 kpc × 2.3 kpc region of M31. Saglia et al (2018) find that the bar and bulge are similar in age and [α/Fe] maps, but the bar stands out in metallicity, approximately solar, in contrast to the metal-rich bulge.…”
Section: Introductionmentioning
confidence: 76%
“…But exactly where are the velocity gradients enhanced? Previous studies have found that the velocity gradients coincide with the dust lane, i.e., on the leading side of the bar (see, e.g., Zurita et al 2004 andFeng et al 2022 for studies on NGC 1530 and M31, respectively).…”
Section: Comparison To the Co Mapmentioning
confidence: 90%
“…Velocity jumps reaching ∼100−150 km s −1 have been found using Hα, [N II], [S II], H I, and CO (Pence & Blackman 1984;Reynaud & Downes 1998;Laine et al 1999;Mundell & Shone 1999;Weiner et al 2001;Zurita et al 2004), and even up to 200 km s −1 (Zánmar Sánchez et al 2008;Feng et al 2022). Thus, our results are comparable to previous observational studies on the other objects.…”
Section: Velocity Jumpsmentioning
confidence: 94%